QUALITY ASSESSMENT OF BAKERY PRODUCTS IN PRODUCTION (Multidisciplinary Journal of Science and Technology, 2026)
Bakery products impose strict requirements on manufacturers. Today, it's not enough to produce only mass-produced varieties of bread and bakery products. To survive and be successful, it's necessary to produce a wide range of products. Bread provides 50% of the human body's need for B vitamins. The vitamin content of bread depends on the type of flour. Bread made from wholemeal flour has the highest vitamin content, but the vitamin content decreases due to their destruction during baking (up to 20-30% is lost).Bread is also an important source of minerals. It contains potassium, phosphorus, magnesium, and, in somewhat smaller quantities, sodium, calcium, chlorine, and others. Lower-grade breads contain more minerals.Currently, the issue of high-quality bakery products is becoming increasingly pressing. This article presents the results of laboratory studies, comparative evaluations, and quality assessments of bakery products. Two types of bread were examined , and an organoleptic assessment of bread quality was conducted, along with studies of physicochemical parameters (crumb moisture, crumb acidity, and crumb porosity).